Nephritogenic antigen determinants in epidermal and renal basement membranes of kindreds with Alport-type familial nephritis. - Kashtan, C (1986)
We probed epidermal basement membranes (EBM) of acid-urea denatured skin from members of kindreds with Alport-type familial nephritis (FN) for the presence of antigens reactive with Goodpasture sera (GPS) and serum (FNS) from an Alport patient who developed anti-glomerular basement membrane (GBM) nephritis in a renal allograft. By immunoblotting, GPS reacted primarily with the 28,000 molecular weight (mol wt) monomer but also the 24,000 mol wt and 26,000 mol wt monomers of the noncollagenous globular domain (NC1) of type IV collagen from normal human GBM, while FNS identified only the 26,000-mol wt monomer. FNS reacted with EBM of 12 controls and nine unaffected male kindred members but not EBM of eight affected males. Five affected females exhibited interrupted reactivity of FNS with EBM. GPS showed variable reactivity with EBM and was not discriminating with respect to Alport-type FN. FNS did not stain renal basement members of five affected males. However, the EBM, tubular basement membrane, and Bowman's capsules of affected males contained antigens reactive with GPS. These immunochemical studies suggest that the FNS antigen is distinct from Goodpasture antigen(s). The expression of FNS antigen located on the NC1 domain of type IV collagen is altered in basement membranes of patients with Alport-type FN, and the distribution of this antigenic anomaly within kindreds suggests X-linked dominant transmission of a defective gene.